Prevention of postpneumonectomy bronchial fistulas in thoracic oncosurgery - Hrubnyk, V. V.; Dushko, M. Ye. (Zaporozhye Medical Journal, 2022)
Pneumonectomy is a widely used surgical intervention in thoracic oncosurgery. One of the most severe complications of this operation is postpneumonectomy bronchial fistula (PBF), and the incidence of PBF after “right-sided” operations is 2.5–5.0 times higher than after “left-sided” ones. There is no single approach to the prevention of this complication. It is obvious that it is necessary to find the most effective methods of PBF prevention in thoracic oncosurgery, especially after “right-sided” operations. Aim. To study the efficiency of diaphragmoplasty of the right main bronchial stump after pneumonectomy performed with lymphadenectomy for malignant neoplasms of the lung. Materials and methods. A retrospective analysis of the treatment including 38 patients operated on in the volume of right-sided pneumonectomy with lymphadenectomy up to D2–D3a from 2014 to 2021 was carried out. Patients were divided into 2 groups: group 1 – patients for whom the stump of the right main bronchus was closed by the Sweet techniques using mechanical suturing devices followed by a reinforcing layer of interrupted Vicryl sutures (n = 28); group 2 – patients who underwent diaphragmoplasty for the stump of the right main bronchus according to D. A. Chichevatov with our modification (n = 10) after suturing by the same techniques. Results. In group 1, PBF occurred in 25 %, the rate of PBS was 0 % in group 2. Conclusions. Diaphragmoplasty for the stump of the right main bronchus according to D. A. Chichevatov with our modification after pneumonectomy performed with lymphadenectomy up to D2–D3a reduced the incidence of PBS by 25 %.